The importance of interview in psychological evaluation in the transit context (Research, Society and Development, 2021)
This article aims to verify the importance of the interview in the process of psychological assessment in the context of traffic. Therefore, a qualitative study was performed with a narrative literature review of articles found in the electronic databases BVS-Psi, Scielo and Google Scholar, and normative resolutions of the Federal Council of Psychology that addressed the theme of Traffic Psychology and Psychological Assessment. Traffic Psychology in Brazil emerged from the need to understand and assess the behavior of drivers in order to contribute to safer traffic. In this sense, psychological assessment became mandatory in the drivers license process and, as a historical consequence, it became the priority activity of traffic psychologists. There is, however, a confusion on the part of many people, including psychologists, between psychological assessment and psychological testing, as many professionals use only psychological tests in the assessment process. It was found that conducting the interview provides more efficiency to the process and greater security of results, supporting the professional's decision-making and making the work ethical, which contributes to transit in the country. It is through the interview that there is the possibility of a broader assessment and greater reliability in the data obtained of the candidate or driver. Thus, it is necessary to constantly update and train the psychologist with regard to the technique and procedures of psychological assessment, so as not to reduce the assessment in testing, so as not to cause harm to the people evaluated or to society.